X2 VVER-1000 benchmark revision: Fresh HZP core state and the reference Monte Carlo solution. (1st September 2020) - Bilodid, Yuri; Fridman, Emil; Lötsch, Thomas
Highlights: Benchmark based on the operational data of an actual VVER-1000 unit. Fresh core hot zero power experiments. Detailed core definition. Serpent Monte Carlo reference solution. Comparison with the measured data. Abstract: The X2 VVER-1000 benchmark provides a unique set of the operational data of a VVER-1000 reactor. This includes fresh core hot zero power (HZP) experiments, operational history of first four fuel cycles, and information on the operational transients occurred on the unit during first cycles. Since a publication of the initial versions of the benchmark, numerous updates, corrections and refinements become available. The current paper is a first in a series of publications on the revised X2 VVER-1000 benchmark. It is dedicated to the fresh core HZP experiments and includes description of the fuel and core geometries, the material compositions, description and results of the measurements taken during fresh core start-up. In addition, the paper includes the reference Monte Carlo solution for the HZP experiments obtained with Serpent 2. The calculated and measured values are in a good agreement. Further extension of the benchmark definition is foreseen in the near future.